Lintel placed over the door jambs of the sanctum of Harshnath Temple - Temples of India Project Team (Jio Institute, 2024)
The lintel over the door jambs of the sanctum of the Harshnath Temple depicts the trio of Brahma, Vishnu, and Mahesha, with Vishnu occupying the central position. Art historian Ambika Dhaka is of the view that this lintel might have been a later replacement of the original lintel featuring an image of Lakulisha at the centre. Above the lintel, there are architectural fragments confirming a later-day renovation made from reused architectural pieces.